To Float or to Fix: Evidence on the Impact of Exchange Rate Regimes on Growth - Levy-Yeyati, Eduardo; Sturzenegger, Federico (American Economic Review, 2003)
We study the relationship between exchange rate regimes and economic growth for a sample of 183 countries over the post-Bretton Woods period, using a new de facto classification of regimes based on the actual behavior of the relevant macroeconomic variables. In contrast with previous studies, we find that, for developing countries, less flexible exchange rate regimes are associated with slower growth, as well as with greater output volatility. For industrial countries, regimes do not appear to have any significant impact on growth. The results are robust to endogeneity corrections and a number of alternative specifications borrowed from the growth literature.